The Role of Clinical Instructor in Nursing Clinic Practice - Maria Agustina Ermi Tri Sulistiyowati; Emirensiana Anu Nono; Maria Karolina Selano (Jurnal Kesehatan, 2021)
The rapid development of technology in the field work does not only require that college graduates have extensive knowledge, but also have professional skills that are ready to be used in the job field. The achievement of student skills in clinical practice cannot be separated from the role of clinical instructor. Clinical instructors have a responsibility to ensure students learn and gain clinical skills experience. The nurses who are appointed as clinical instructor have a dual role. They are not only as clinical instructor, but also carrying out roles as team leaders, room manager and implementing nurses. This can have an impact on the implementation of the role as clinical instructor. This research aims to determine the role of clinical instructor at St. Elizabeth Hospital Semarang. This type of research is qualitative research. The main informants in this study are clinical instructor, while the triangulation informants are students who carry out clinical practice at St. Elisabeth Hospital Semarang. Informants were taken by using purposive sampling technique. Data collection was carried out by in-depth interviews. The research resulted in 2 themes, the role as an educator and as a motivator.